Is the frame the name of the game? The influence of message framing on fitness class attendance and performance - Lundeberg, Pamela J., author; Graham, Dan, advisor; DeLosh, Ed, committee member; Slejko, Gina, committee member; Wickens, Chris, committee member (Colorado State University. Libraries, 2020)
Despite the inarguable benefits of exercise, less than twenty percent of Americans meet the ACSM's physical activity (PA) recommendations (CDC, 2017). Many interventions have focused on increasing participation in individual PA activity, but inspiring participation in group fitness classes may be more advantageous than promoting individual PA, as group fitness offers the added benefits of social support and accountability (Estabrooks, 2000). This dissertation sought to determine the most effective manner to market group fitness classes by testing the effect of message framing on college students' attendance of a variety of group fitness classes. Furthermore, this study considered the influence that exposure to message framing may have on individuals' mindsets and, specifically, how mindsets induced via message framing may affect individuals' performance in group fitness classes. Therefore, two experiments were conducted to independently examine message framing's effect on individuals' attendance of and experiences during fitness classes. In experiment 1, 189 participants read descriptions of four different fitness classes – each of which included a different type of message framing (gain vs. loss framing) and different framing content (appearance vs. health outcomes) – and selected one of the four classes to attend. Accordingly, participants read descriptions of four unique classes that featured (1) appearance-related gain framing, (2) appearance-related loss framing, (3) health-related gain framing, and (4) health-related loss framing. Participants in experiment 1 were required to attend the class of their choosing; upon completion of the class, participants self-reported their enjoyment of and effort in the fitness class they completed. In experiment 2, 131 participants attended the same fitness class – a 45-minute highly standardized barbell class – and were randomly assigned to one of the four framing conditions included in study 1 (appearance gain, appearance loss, health gain, and health loss) or a control condition that included no framing. Immediately prior to starting the fitness class, participants viewed a class description that included the framing manipulation (i.e., class description featured one of the five framing options). Participants wore an Actigraph accelerometer (i.e., an activity tracker) during the class, allowing for objective assessment of participants' energy expenditure during the class. In experiment 1, participants overwhelming chose to attend classes whose descriptions included appearance-related gains. Likewise, participants were indeed more likely to select gain frames over loss frames. Participants also reported exerting more effort in classes whose descriptions featured gain framing. However, participants' reported enjoyment of classes did not differ by framing condition – i.e., the framing included in the class descriptions did not influence the level of enjoyment participants reported in the four differently-framed classes. While participants reported exerting more effort in gain-framed classes in experiment 1 (that is, participants perceived themselves as exerting more effort in gain-framed classes), participants' objective energy expenditure (i.e., minutes spent in moderate-to-vigorous PA and caloric expenditure, as measured via actigraphy) was not affected by exposure to differently-framed messages in experiment 2. Likewise, participants' self-reported effort did not differ by framing condition in experiment 2. However, participants exposed to gain-framed descriptions reported greater enjoyment of the fitness class. This research demonstrated that message framing significantly impacted attendance rates of fitness classes – individuals were significantly more likely to attend classes whose descriptions featured appearance-related gain framing (experiment 1). However, message framing did not produce a clear effect on individuals' performance in these fitness classes, as individuals reported exerting more effort in gain-framed classes (experiment 1) but did not objectively exert more effort (experiment 2), highlighting the need for additional research in this area to disentangle how message framing may influence individuals' experiences during group fitness classes.